Topical Breast Milk Care and Open Care for Umbilical Cord Release Time - Anita, Nur; Wahyuddin, Munadiah; Immawanti, Immawanti; Nasra, Nasra (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2023)
The neonatal mortality rate in Indonesia is still quite high, one of the causes is neonatal infections, namely omphalitis and sepsis. In neonates, the umbilicus is the most vulnerable area for bacterial colonization, therefore correct umbilical cord care is important to prevent infection during the neonatal period. One method used to care for the umbilical cord is topical application of breast milk. Breast milk can speed up the process of shedding the umbilical cord through polymorphonoclear leukocytes in the umbilical cord, photolytic enzymes and other immunological compounds. objective To determine the effect of umbilical cord care using topical breast milk and open methods on the time of umbilical cord removal at the Binanga Community Health Center in 2021. Method This research uses the Quasy Experiment research method, a single treatment design (One Shot Case Study). The population in this study were newborn babies. Sampling was carried out using a total sampling technique, obtaining 30 respondents. Data collection was carried out using questionnaires and observation sheets. The data that has been collected is then processed and analyzed using the SPSS version 20 statistical program and analyzed using Mann Whitney. Result Of research shows that there is an influence of umbilical cord care using topical and open breast milk on the length of umbilical cord removal at the Binanga Community (p=0.005).